Pseudoaneurysm of the facial artery occurred after mandibular sagittal split ramus osteotomy - Jo, H.-W. (Springer-Verlag, 2012)
INTRODUCTION: Pseudoaneurysms are caused by rupture of arteries with extravasation of blood. The compressed perivascular tissue forms the wall of aneurysmal sac. Pseudoaneurysm directly related with surgical procedure of sagittal split ramus osteotomy (SSRO) was reported quite rarely especially related with facial artery during the vertical osteotomy. CASE REPORT: SSRO was carried out for a 19-year-old male; the patient visited the emergency room with notable swelling 3 weeks after the surgery. We experienced severe intra-oral bleeding with surgical exploration. Angiography revealed a pseudoaneurysm of the right facial artery that might be related with vertical osteotomy over lateral cortex of the mandibular body during orthognathic surgery. This implies that the minor vascular trauma from vertical osteotomy of the mandibular body during the conventional orthognathic surgery might cause later development of pseudoaneurysm.